Ketangguhan Retak Komposit Epoxy - Serbuk Cangkang Kerang - Yohanes Suyoko; Burhan Ibnu Mubtadi (Politeknosains, 2020)
Composite is a new material resulting from a combination of two or more materials. Each of composite materials has advantages that will reduce or even eliminate the deficiencies of other materials. Fillers are given to strengthen the particle shaped matrix. This study aims to determine the effect of the addition of scallop powder in the epoxy matrix to the fracture toughness of the epoxy-scallop powder composite. The composite matrix is Eposchon products of PT. Justus Kimia Raya and its reinforcing material are scallop powder with a size of 40 mesh passes. The conventional method is used to make composites, where the scallop powder is mixed in epoxy resin with variations in weight fraction of 0%, 5%, 10% and 15%. Each composition was mixed with a mechanical stirrer for 15 minutes at 500 rpm and a temperature of 40 ° C. At the last minute the stirrer rotation is lowered at 100 rpm while adding a hardener (catalyst). The next process is pouring the mold followed by curing in an oven at 90 ° C for 2 hours. The specimen is then tested for fracture toughness according to ASTM D5045 standard. The test results showed that there was an increase in fracture toughness in all additional weight fractions of the shell powder. The biggest increase occurred in the addition of 5% by weight fraction, where the fracture toughness increased by 178.38% (1.03 MPa.m1/2).